UJI ANTIHYPERGLIKEMIK EKSTRAK ETANOL AKAR TEMBELEKAN (Lantana camara L.) TERHADAP KADAR GLUKOSA DARAH MENCIT JANTAN (Mus musculus) - Sulistiani, Oktaviana Dewi; Kartika, Rudi; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2016)
Phytochemical screening from extract ethanol of tembelekan root has been carried out, its showed the presence of alkaloids, phenol, sapponin and flavonoids. Antihyperglikemik test from ethanol extract of tembelekan root had been done through experiment in laboratory, each doses 13,95, 27,90 and 55,80 mg/Kg BW was given orally at male mice to know the effect of antihyperglikemik toward the decrease of glukosa level in male mice's blood. The measurement at glucose level inside male mice's blood was done on 0th, 8th and 18th day by using glucometer and glucotest strip devices. giving the variation of doses etanol extract of tembelekan root, its showed at doses 55,80 mg/Kg BW could decrease the glucose level until 61,57%. From this research showed the result of decrease of glucose level because the effect from ethanol extract of tembelekan root that distributed inside the blood. Keywords : Tembelekan root, antihyperglikemic, blood glucose, mice, alloxan